Looney tunes collection best of tweety and syivester Volume 1 - Warner Bros (Burbank, CA Distributed by Warner Home Video, 2007)
Features 60 cartoons, including Bugs and Daffy shorts, Looney Tune-ized fairy tales, and archived productions featuring early versions of the characters
Title from container
2
Keywords: Bugs Bunny (Fictitious character) -- Drama; Porky Pig (Fictitious character) -- Drama; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs